Application of Hand Held Fan Therapy and Orthopneic Position to Reduce Dyspnea in Congestive Heart Failure (CHF) Patients: Case Report - Salsabilla, Sausan Zahrah Salwa; Platini, Hesti; Sari, Eka Afrima (Universitas Padjadjaran, 2025)
Introduction: Congestive Heart Failure (CHF) is a condition in which the heart is unable to pump blood effectively to meet the body’s needs, resulting in decreased cardiac output. This leads to fluid accumulation in the lungs due to increased pulmonary venous pressure, which subsequently triggers pulmonary edema. Pulmonary edema causes impaired oxygen diffusion in the alveoli, resulting in dyspnea as the primary complaint in CHF patients. The main nursing problem that arises is impaired gas exchange, indicated by an increased respiratory rate, decreased oxygen saturation, and the use of accessory respiratory muscles. To help address impaired gas exchange in CHF patients, non-pharmacological therapies such as the use of a hand-held fan and the implementation of an upright sitting position (orthopnea position) can be utilized. Purpose: To evaluate the effectiveness of the hand-held fan and orthopneic position interventions in CHF patients experiencing shortness of breath. Methods: This study employed a case study approach based on observation, interviews, and medical record reviews. The interventions hand-held fan and orthopneic position were administered over three days, with each session lasting 5 minutes. Results: Following the interventions, respiratory rate decreased from 30 breaths per minute to 25 breaths per minute, and oxygen saturation increased from 95% to 98%. The patient reported feeling more relieved, comfortable during breathing, and able to sleep more easily, although occasional shortness of breath persisted. Discussion: The interventions are physiologically beneficial: the orthopneic position helps reduce venous return to the heart, thereby lowering pulmonary pressure, while hand-held fan therapy alleviates the perception of breathlessness through sensory stimulation of the face, which activates the V2 branch of the trigeminal nerve. Conclusion: The combination of hand-held fan therapy and the orthopneic position is effective in relieving dyspnea, reducing respiratory rate, and improving oxygen saturation in patients with congestive heart failure